L’histoire muette - Sabine Ehrmann (Projets de Paysage)
For 25 years, the Observatoire photographique national du paysage, or OPNP, (National Photographic Observatory of the Landscape) has generated an unprecedented number of visual documents of contemporary French landscapes. A pressing question today is the future and possible use of this mass of documents. The suggestion in this article is to envisage using them for historical research. The creation of the landscape observatories included, to a certain extent, a rather radical and innovative proposition from a historiographical standpoint : that of writing history with photographic images. However, such an historical undertaking does not imply the same conditions as the representation of the landscape but rather the elaboration of a didactic tool able to describe what unavoidably eludes photography : the reasons behind changes or the absence of changes ; or at least some assumptions concerning such reasons.